Screening for SNPs and haplotypes in the CYP3A7 gene in Chinese populations. (June 2007) - Du, Jing; Shi, Yongyong; Zhang, Aiping; Wang, Lei; Xuan, Jiekun; He, Guang; Xu, Lingyun; Xu, Mingsheng; Shu, Anli; Yu, Lan; Li, Xingwang; Meng, Junwei; et al.
Objective : To determine the frequencies and haplotypes of the cytochrome P450 (CYP)3A7 gene in three Chinese ethnic groups, namely, Han, She and Dong.Methods : SNP analyses of the CYP3A7 gene were carried out on three groups of healthy Chinese subjects consisting of 539 Han, 264 She and 273 Dong subjects, using direct sequencing. Linkage disequilibrium, haplotype inference and Hardy––Weinberg equilibrium were also determined for these samples.Results : Significant differences were observed in the distribution of SNP rs2257401 ( CYP3A7*2 ), SNP 1227 T>C (Novel), SNP rs4646468 and SNP rs10211 between the Han, She and Dong groups.Conclusion : Some allele and haplotype frequencies show variation among groups, highlighting the need to analyze clinically relevant SNPs and haplotypes in a variety of different racial groups within the Chinese population as well as in other ethnic groups. These results suggest that genetic polymorphisms in the CYP3A7 gene in the Han, She and Dong populations may contribute to interindividual as well as intra-ethnic differences in response to the clearance of CYP3A7  substrates.